2003
DOI: 10.1194/jlr.m300160-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the unnatural anticancer lipid safingol, l-threo-dihydrosphingosine, in cultured cells

Abstract: We studied the metabolism of radioactively labeled safingol ( L -threo-dihydrosphingosine) in primary cultured neurons, B104 neuroblastoma cells, and Swiss 3T3 fibroblasts, and compared it to that of its natural stereoisomer D -erythro -dihydrosphingosine. Both sphingoid bases are used as biosynthetic precursors for complex sphingolipids, albeit to different rates. Whereas a considerable amount of the natural sphingoid base is also directed to the catabolic pathway (20-66%, cell type dependent), only a minor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…These values were comparable to 3.8-8.6 µM, which is the activity reported for safingol against a panel of six HNSCC cell lines including 22B [28]. It has been shown that despite its nonnatural stereochemistry, safingol is recognized and metabolized preferentially by enzymes of the sphingolipid biosynthetic pathway [29].…”
Section: Discussionsupporting
confidence: 51%
“…These values were comparable to 3.8-8.6 µM, which is the activity reported for safingol against a panel of six HNSCC cell lines including 22B [28]. It has been shown that despite its nonnatural stereochemistry, safingol is recognized and metabolized preferentially by enzymes of the sphingolipid biosynthetic pathway [29].…”
Section: Discussionsupporting
confidence: 51%
“…We and others have demonstrated that safingol is metabolized into Lthreo-dihydroceramide and/or L-threo-ceramide variants, both in vitro (14, 74 -77) and in vivo (78), with some disagreement between the data, perhaps due to species or cell line type variation. L-threodihydroceramide and/or L-threo-ceramide was incorporated into dihydrosphingomyelin or sphingomyelin but not readily glucosylated, thus demonstrating stereo-specific metabolic restrictions (14,74,75,78). Because we and others have demonstrated that high levels of one or both of these L-threo sphingolipids accumulate even at low, nontoxic safingol concentrations in vitro (14), it is possible that L-threo sphingolipids may synergize the cytotoxicity of native de novo-generated ceramide species, including dihydroceramides (79,80), by specific interference with their catabolism or may interfere with the ability of native ceramide species to activate atypical protein kinase Cs.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that despite its nonnatural stereochemistry, safingol (39) was recognized and metabolized preferentially by enzymes of the sphingolipid biosynthetic pathway [96]. Safingol (39) was mainly metabolized to dihydroceramide (4 ) and dihydrosphingomyelin, whereas most of its physiological counterpart sphinganine (3) was transformed in cultured cells into fatty acids, sphingomyelin, and complex gangliosides.…”
Section: Sphingosine and Analogsmentioning
confidence: 99%